Feasibility of integrative games and novel therapeutic game controller for telerehabilitation of individuals chronic post-stroke living in the community. Issue 5 (3rd July 2020) - Burdea, Grigore C.; Grampurohit, Namrata; Kim, Nam; Polistico, Kevin; Kadaru, Ashwin; Pollack, Simcha; Oh-Park, Mooyeon; Barrett, A.M.; Kaplan, Emma; Masmela, Jenny; Nori, Phalgun
ABSTRACT: Background: Intensive, adaptable and engaging telerehabilitation is needed to enhance recovery and maximize outcomes. Such services may be provided under early supported discharge, or later for chronic populations. A novel virtual reality game-based telerehabilitation system was designed for individuals post-stroke to enhance their bimanual upper extremity motor function, cognition, and wellbeing. Objectives: To evaluate the feasibility of novel therapeutic game controller and telerehabilitation system for home use. Methods: Individuals chronic post-stroke and their caregivers were recruited (n = 8 + 8) for this feasibility study. One was a screen failure and seven completed 4 weeks (20 sessions) of home-based therapy with or without remote monitoring. Standardized clinical outcome measures were taken pre- and post-therapy. Game performance outcomes were sampled at every session, while participant and caregiver subjective evaluations were done weekly. Results: There was a 96% rate of compliance to protocol, resulting in an average of 13, 000 total arm repetitions/week/participant. Group analysis showed significant ( p <.05) improvements in grasp strength (effect size [ES] = 0.15), depression (Beck Depression Inventory II, ES = 0.75), and cognition (Neuropsychological Assessment Battery for Executive Function, ES = 0.46). Among the 49 outcome variables, 36 variables (73.5%) improved significantly ( p = .001, binomial sign test). Technology acceptance was very good with system rating by participants at 3.7/5 and by caregivers at 3.5/5. Conclusions: These findings indicate the feasibility and efficacy of the system in providing home-based telerehabilitation. The BrightBrainer system needs to be further evaluated in randomized control trials and with individuals early post-stroke.